1988
DOI: 10.1530/jrf.0.0830829
|View full text |Cite
|
Sign up to set email alerts
|

Effects of donor age on urinary chemosignals that influence the timing of first oestrus in young female house mice, Mus domesticus

Abstract: The effects of donor age on the effectiveness of puberty-influencing urinary chemosignals in wild house mice was tested in a series of 3 experiments. The chemosignal from male mice that accelerates puberty was present in the urine from about the time of puberty and throughout the normal lifespan, but declined about 1 year of age. Oestrous females released a substance in their urine that accelerates puberty in young females. This substance remained effective from first oestrus until over 1 year of age, although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…This urine was used as the control carrier solution because no MUP could be detected either by gel electrophoresis or by colorimetric protein assay. In addition, a previous study has demonstrated that prepubertal male urine by itself has no influence on female puberty onset (Drickamer, 1988). No difference could be observed in body weight prior to the treatments (U = 60-5, P = 0 5067).…”
Section: Resultsmentioning
confidence: 73%
“…This urine was used as the control carrier solution because no MUP could be detected either by gel electrophoresis or by colorimetric protein assay. In addition, a previous study has demonstrated that prepubertal male urine by itself has no influence on female puberty onset (Drickamer, 1988). No difference could be observed in body weight prior to the treatments (U = 60-5, P = 0 5067).…”
Section: Resultsmentioning
confidence: 73%